Facilitating Diagnostic Competences in Simulations in Higher Education - Nicole Heitzmann; Tina Seidel; Ansgar Opitz; Andreas Hetmanek; Christof Wecker; Martin R Fischer; Stefan Ufer; Ralf Schmidmaier; Birgit Neuhaus; Matthias Siebeck; Kathleen Stürmer; Andreas Obersteiner; et al. (EARLI, 2019)
Diagnosis is a prerequisite for successful professional problem-solving: A physician identifies an appropriate treatment based on a diagnosis of the patient's disease, and a teacher selects an appropriate learning task based on an assessment of the student's prior knowledge. Education in academic professions such as medicine or teaching is often focuses on the acquisition of conceptual knowledge from lectures and books; opportunities for students to engage in practical diagnostic situations are typically rare. However, applying such conceptual knowledge in diagnostic activities is regarded as necessary for developing diagnostic competences. In this article, we focus on simulations in which students can actively engage in practicing diagnostic activities concerning cases from professional practice. We review and link research perspectives on diagnostic competences, their components and their development. This is partly done by exploring the commonalities and differences in research on diagnostic competences in medicine and teaching. Then, we present approaches to simulation, followed by different types of instructional support in such simulations. In particular, we focus on different forms of scaffolding during problem-solving, and on the possibly complementary roles of expository forms of instruction in these kinds of environments. Building on the perspectives reviewed, we propose a framework for fostering diagnostic competences in simulations in higher education and outline an interdisciplinary research approach concerning the instructional design of such simulations.